Real‐time hemodynamic effects of 1:100, 000 and 1:200, 000 injectable epinephrine and placement of topical 1:1000 epinephrine pledgets in patients undergoing endoscopic sinus and skull‐base surgery: a randomized, prospective study. Issue 2 (9th December 2019) - Ahmed, Omar G.; Yu, Justin; Choi, Jonathan S.; Yim, Michael T.; Yoshor, Daniel; Takashima, Masayoshi
Abstract : Background: Intranasal injection of epinephrine and placement of topical epinephrine pledgets are methods to improve visualization during endoscopic sinonasal surgery. Studies comparing the hemodynamic effects of these vasoconstrictors using intraoperative arterial line monitoring are lacking. Methods: Twenty‐eight patients undergoing endoscopic skull‐base surgery were enrolled in a prospective, randomized study. Patients were randomized to have either 2 mL of 1:100, 000 or 2 mL of 1:200, 000 epinephrine injected intranasally. Hemodynamic parameters, including pulse, systolic blood pressure (SBP), diastolic blood pressure (DBP), and mean arterial pressure (MAP), were collected using intraoperative arterial line monitoring for 5 minutes. Afterward, 1:1000 topical epinephrine‐soaked pledgets were placed in both groups, and the same parameters were collected for another 5 minutes. Results: There was no statistical difference in change in pulse, SBP, DBP, and MAP between the 1:100, 000 and 1:200, 000 epinephrine groups. However, epinephrine injections did cause an increase in all hemodynamic parameters when compared with baseline ( p < 0.05). Topical epinephrine pledgets placed after injection of epinephrine did not have any significant hemodynamic effects, except for 2 of 28 patients who had a >75‐mmHg increase in SBP. No preoperative characteristics were identified that predicted sensitivity to epinephrine. Conclusion: There is no statistical difference in changes in hemodynamic parameters between injecting epinephrine 1:100, 000 compared with 1:200, 000 during endoscopic sinonasal surgery. In a subset of patients, placement of topical 1:1000 epinephrine pledgets had significant hemodynamic elevation requiring intervention and thus should be used judiciously depending on patient comorbidities.